A new species of Hibiscus (Malvaceae) from the state of Oaxaca - Fryxell, Paul A. (Instituto de Ecología, A.C., 1989)
A new species from western Oaxaca, Hibiscus tenorii, is described and illustrated. It is related to a group of western and southern Mexican species of Hibuscus with red, tubular corollas and with androecium and styles prominently exserted.